Hyperosmolar Therapy for Diabetic Hyperosmolar Ketoacidosis - Heldeweg, Micah LA; Drossaers, Joris R; Berend, Kenrick (European Journal of Case Reports in Internal Medicine, 2022)
Hyperglycaemic hyperosmolar state (HHS) and diabetic ketoacidosis (DKA) features can occur simultaneously in 27% of diabetic emergencies and have a two-fold increased risk of death. Despite the high prevalence of this combination, recommended treatments from leading guidelines may not be compatible with the clinical picture. A 36-year-old man presented with explicit concurrent HHS and DKA. The recommended treatment with simultaneous insulin and volume repletion was followed but resulted in an excessively rapid decline in serum osmolarity. Hyperosmolar therapy (NaCl 3%) was initiated to mitigate the risk of potentially fatal cerebral osmotic shifts. The concomitant presence of DKA and HHS leads to a treatment dilemma with a high risk of excessive osmolarity shifts. More evidence is needed, but it is reasonable to initiate tailored treatment to avoid osmolarity reduction rates exceeding the hypernatraemia-based limit of 24 mOsm/l/day. Hyperosmolar therapy can be considered but requires frequent monitoring of electrolytes and osmolarity.